PENGARUH DISIPLIN KERJA, ROTASI KERJA DAN STRESS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT EXCELITAS TECHNOLOGIES BATAM : PENGARUH DISIPLIN KERJA, ROTASI KERJA DAN STRESS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT EXCELITAS TECHNOLOGIES BATAM - Samosir, Erina Safitri; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2024)
Productive employees with good work results will certainly make the company better. However, creatingproductive and high-quality employees is certainly not an easy matter for a company, where the companymust of course think about the best strategy to stimulate work enthusiasm. Many factors can influence anemployee's productivity, one of which is work discipline, work rotation and work stress. This research isquantitative research. The population in this study were all employees of the Department Detection, LineTPMI and SMD APD at PT Excelitas Technologies Batam, totaling 113 people using a saturated samplingtechnique. Based on the results of statistical tests, it is known that the variables of work discipline, workrotation, work stress and work productivity are normally distributed, where multicollinearity andheteroscedasticity do not occur in the independent variables. The results of the t-test show that the workdisciplines partially no effect on work productivity with a significance rate of 0.721 > 0.05. Work rotationvariable is partially no effect on work productivity with significance levels 0.293 > 0.05. Work stressvariable partially significantly affect on work productivity with significance levels Working environment,work discipline and work stress simultaneously affect employee performance with significance levels 0.001< 0.005. Work disciplines, work rotation, and work stress simultaneously affect on work productivity withsignificance levels 0.001 < 0.005.